Osteonecrosis of the Jaw after Covid-19 - Sh. A., Boymuradov; Y. H., Kurbanov; Sh., Yusupov Sh.; Sh., Azadov M.; K. S., Asrorova (Journal of Innovation in Education and Social Research, 2024)
COVID-19 is currently causing a global pandemic. With the increasing number of patients, there has been a slight rise in the incidence of various complications. Specifically, infectious and inflammatory diseases of the face and jaw are observed in COVID-19 patients during the early infectious stages of the disease as well as in the later stages. Previous literature has mentioned cases where changes in the oral cavity, such as ulcers, rashes, and inflammation of salivary glands, were identified as signs or complications of COVID-19. The conditions discussed in this article represent a serious complication of COVID-19, markedly different from the typical course of osteomyelitis, wherein patients experience a predominance of long-term, chronic-progressive, atrophic processes. The treatment proved somewhat ineffective due to local chronic inflammation and metabolic, microcirculatory, immune, and coagulation disorders in patients.